Soledad Acosta de Samper and her role in translation in the 19th century Colombia - Aguirre Gaviria, Beatriz Eugenia (Íkala, Revista de Lenguaje y Cultura, 2004)
This is a reflection about the relationship between translation and the process of national formation in Colombia. The theories of Benedict Anderson and Gideon Toury, among others, serve as the general theoretical framework. There is an analisis of excerpts taken from translations done by 19th century Colombian translators. On secting is dedicated to the translation work done by Soledad Acosta de Samper on a French text written by Paul Leroy-Beaulieu about women´s jobs and education in France. The article closes exposing Acosta´s conclusions about her study of the French text and its relation with the situation of Colombian women in issues such as the State, family, education, and jobs. Received: 02-12-03 / Accepted: 02-03-04 How to reference this article: Aguirre Gaviria, B. E. (2004). Soledad Acosta de Samper y su papel en la traducción en Colombia en el siglo XIX. Íkala. 9(1), pp. 233 – 267